Lavender Aromatherapy and Distraction Effectively Reduce Anxiety of Chemotherapy Patients - Estichoma, Siti; Mawaddah, Nurul; Mujiadi, Mujiadi (Promotion and Prevention in Mental Health Journal, 2022)
Excessive anxiety in chemotherapy patients can affect the patient's motivation to carry out chemotherapy. Pharmacological therapy to reduce patient anxiety has many unwanted side effects. Therefore, non-pharmacological treatment is needed because it has few side effects, one of which is lavender aromatherapy. The purpose of this study was to determine the impact of giving aromatherapy in reducing the anxiety of chemotherapy patients at Lavalette Hospital. This type of research is quasi-experimental, with the pretest-postest control group design used in this study. The samples in this study were 30 chemotherapy patients at Lavalette Hospital at the time of the research. Data analysis used a paired T-test technique. Data analysis tests the average anxiety level in the intervention group, which was 16.60 with a standard deviation of 2.530, while for the control group, which used distraction techniques, the average was 19.80 with a standard deviation of 2.569. Statistical test results obtained a sig value (2tailed) of 0.002 (P <0.05). The results obtained are differences in anxiety reduction with distraction therapy and lavender aromatherapy therapy. The provision of lavender aromatherapy is more effective than the distraction technique, as evidenced by the difference in the average anxiety reduction of 1.1 points. It is expected that aromatherapy therapy can be applied to chemotherapy patients with anxiety.